Insuficiencia del código orgánico integral penal en cuanto a sanciones para los servidores públicos que incumplan sus deberes y obligaciones en relación a la preservación de los indicios, la escena del hecho y cadena de custodia - González Mendoza, Gilbert Efraín (2016)
The Ecuador is a democratic country which guarantees the rights of citizens, in the same way it complies with due process in all legal areas, which is why this research is based on the correct application of the chain of custody in criminal proceedings, so that in this way is valued correctly test and there are no anomalies in the administration of Justice. In our country there are no completely adequate centers for the preservation of the evidence remains which tended has destroyed, lost, damaged, etc., causing great controversy in the assessment of the test, and do not allow a proper appreciation of what had happened, causing a problem in the application of due process. The chain of custody is a procedure established by legal regulations, which is intended to ensure the integrity, conservation and inalterability of elements materials such as documents, samples (organic and inorganic), firearms, projectiles, vanillas, weapons, narcotic drugs and their derivatives, delivered to the forensic laboratories or forensic the authority to discuss and get from experts, technicians or scientists, an expert concept. From the location, locking, collection, packing and transfer of evidence at the scene of the accident, to the presentation to the debate, the chain of custody must ensure that the procedure has been successful, and that the evidence collected at the scene, is the same one that is being presented to the Court, or the respective expert opinion. Its importance lies in that ensures perfect management of the material evidence since its identification in the scene, through different laboratories, to the shipping of the forensic results to the appropriate authority. It is important to mention that who compose the chain of custody (surveillance) initially uniformed police personnel, are always the first to arrive at the site or location of the incident, who should avoid as far as possible that the evidence can be manipulated, altered. Etc. Then prepare the respective police party making known to their superiors and authority about what happened. Should be kept control as to identify evidence or evidence, must likewise make in places which fulfil the necessary conditions, avoid losses, thefts, changes, damage, etc. and must be the inalterability of samples, namely pollution, destruction or degradation; then continue with the procedure, officials and persons under whose responsibility are the respective elements of proof during the different stages of the criminal process. Therefore, any official who receive, generate or analyze samples or elements of proof or documents, part automatically of this simple procedure, but must be complied with during the development of the research. It is the responsibility of any official who is involved in the chain of custody process, to General and specific procedures for this purpose. I.e. ignorance of the chain of custody does not exempt from liability to the person of any institution that omit it or forget to at some point. As well as each of officials involved in the process, is responsible for the control and registration, because his performance is direct on the various decisions taken by the Prosecutor or judge, depending on course is, from the stage of the proceedings. The application of the legal rules that govern the chain of custody are accurate as to its preservation procedure and the criteria for their evaluation, not lacking the determination of a standard that determines the penalty for public servants who fail to comply with their duties and obligations in the preservation of evidence, the scene of the event or failure to comply with the lack of chain of custody, and their inadequate management and treatment. As a result or consequence that may result in contamination of the fact or crime scene, alteration of traces, test poor criminal, alteration of the truth of the facts and as such violation of legal norms and guarantees and constitutional principles, and other problems. By what I consider, necessary Integral organic code Penal, inserting sanctions on failure to comply with the preservation of the scene of the fact or evidence and chain of custody, identified administrative and pecuniary sanctions without that it is exempt from civil and criminal compensation has place.